Pierre Carlier, un esprit de finesse - Carlier, Pierre (B@sic, 2022)
Realised in order to pay homage to Pr. Pierre Carlier (departed ten years ago), this volume is a new edition of 31 of his main studies. Readers will find in it the major themes of his research (conducted between 1977 and 2010), between the Mycenaean world and the Classical Greece, with, almost, the study of Greek kingships and the political thought.